Successful Induction of Specific Immunological Tolerance by Combined Kidney and Hematopoietic Stem Cell Transplantation in HLA-Identical Siblings - Fehr, Thomas; Hübel, Kerstin; de Rougemont, Olivier; Abela, Irene; Gaspert, Ariana; Güngör, Tayfun; Hauri, Mathias; Helmchen, Birgit; Linsenmeier, Claudia; Müller, Thomas; Nilsson, Jakob; Riesterer, Oliver; et al. (Frontiers in Immunology, 2022)
Induction of immunological tolerance has been the holy grail of transplantation immunology for decades. The only successful approach to achieve it in patients has been a combined kidney and hematopoietic stem cell transplantation from an HLA-matched living donor. Here, we report the first three patients in Europe included in a clinical trial aiming at the induction of tolerance by mixed lymphohematopoietic chimerism after kidney transplantation. Two female and one male patient were transplanted with a kidney and peripherally mobilized hematopoietic stem cells from their HLA-identical sibling donor. The protocol followed previous studies at Stanford University: kidney transplantation was performed on day 0 including induction with anti-thymocyte globulin followed by conditioning with 10x 1.2 Gy total lymphoid irradiation and the transfusion of CD34+ cells together with a body weight-adjusted dose of donor T cells on day 11. Immunosuppression consisted of cyclosporine A and steroids for 10 days, cyclosporine A and mycophenolate mofetil for 1 month, and then cyclosporine A monotherapy with tapering over 9–20 months. The 3 patients have been off immunosuppression for 4 years, 19 months and 8 months, respectively. No rejection or graft-versus-host disease occurred. Hematological donor chimerism was stable in the first, but slowly declining in the other two patients. A molecular microscope analysis in patient 2 revealed the genetic profile of a normal kidney. No relevant infections were observed, and the quality of life in all three patients is excellent. During the SARS-CoV-2 pandemic, all three patients were vaccinated with the mRNA vaccine BNT162b2 (Comirnaty®), and they showed excellent humoral and in 2 out 3 patients also cellular SARS-CoV-2-specific immunity. Thus, combined kidney and hematopoietic stem cell transplantation is a feasible and successful approach to induce specific immunological tolerance in the setting of HLA-matched sibling living kidney donation while maintaining immune responsiveness to an mRNA vaccine (ClinicalTrials.gov: NCT00365846).